Investigating the status of English as a lingua franca in Southeast Asia intelligibility and comprehensibility of ASEAN Englishes among Filipino college students - Roxas, Jeff B. (Philippine Journal of Linguistics, 2018)
As the Philippines sustains stronger ties with its neighboring Southeast Asian countries in the age of ASEAN integrations, the ability to accommodate to one's variety of English through word and meaning recognition is essential for international understanding. This paper examines the level of intelligibility and comprehensibility of ASEAN Englishes and the factors that influence their understanding. To collect data, the study used close and comprehension test from three listening passages and a semi-structured interview conducted among 47 liberal arts students. The finding showed that ASEAN Englishes are 85.32% intelligible and 87.94% comprehensible. The high rates denote that the use of shred nonstandard pronunciation features enhanced understanding. Listener and textual factors also proved to be among the factors of understanding. Listener and textual factors also proved to be among the factors of understanding. Hence, this suggests that there is an emerging lingua franca within the ASEAN region. Mutual intelligibility, therefore, may help speakers to establish common identity as as ASEAN community and to bring effective cross-cultural communication during ELF interaction.